2020
DOI: 10.3390/scipharm88010012
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Cyclosporine Blood Levels and Area under Blood Concentration Time Curve in Iraqi Bone Marrow Transplant Patients Treated with Neoral® Oral Solution

Abstract: Cyclosporine is a potent immunosuppressive drug. It has a narrow therapeutic index, and therefore the measurement of cyclosporine’s blood concentration is essential to obtain optimal therapy. Measurement of the area under the blood concentration-time curve (AUC) is reflective of total drug exposure. However, for organ transplant patients, the measurement of AUC involves many problems and difficulties. Thus, it is more clinically acceptable to use a single blood sample as a surrogate index of total drug exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The results agreed with what was reached by [19] who indicated a significant increase in the indicators of ALT, AST and ALP when dosed with cyclosporine (CsA) for male laboratory rats, as the researchers showed that hepatotoxicity induced by CsA begins with the imbalance of arachidonic acid and the synthesis of eicosanoids and the release of free radicals, especially hydroxyl radicals that begin In lipid oxidation and secondary activation of physiological antioxidant defenses. It also agreed with the results of [20] who found that cyclosporine caused a significant increase in the levels of AST, ALT and ALP enzymes in blood samples of 54 Iraqi patients. The results agreed with the findings of [21], [22] and [23] that treatment with selenium nanoparticles (Se-NPs) caused a decrease in the values of AST, ALT and ALP enzymes in infected male laboratory rats, which is an indication of inhibition of inflammation and protection of the liver in Infected mice [23] stated that Se-NPs improve STZ dysfunction through its radical scavenging activity, besides its safety and liver tissue function resulting from the role of Se-NPs in treating liver dysfunction and thus lowering the levels of high values of the enzymes AST, ALT and ALP.…”
Section: Effect Of Se-nps and Se-nps + D3 In Immunosuppressed Rats Gi...supporting
confidence: 91%
“…The results agreed with what was reached by [19] who indicated a significant increase in the indicators of ALT, AST and ALP when dosed with cyclosporine (CsA) for male laboratory rats, as the researchers showed that hepatotoxicity induced by CsA begins with the imbalance of arachidonic acid and the synthesis of eicosanoids and the release of free radicals, especially hydroxyl radicals that begin In lipid oxidation and secondary activation of physiological antioxidant defenses. It also agreed with the results of [20] who found that cyclosporine caused a significant increase in the levels of AST, ALT and ALP enzymes in blood samples of 54 Iraqi patients. The results agreed with the findings of [21], [22] and [23] that treatment with selenium nanoparticles (Se-NPs) caused a decrease in the values of AST, ALT and ALP enzymes in infected male laboratory rats, which is an indication of inhibition of inflammation and protection of the liver in Infected mice [23] stated that Se-NPs improve STZ dysfunction through its radical scavenging activity, besides its safety and liver tissue function resulting from the role of Se-NPs in treating liver dysfunction and thus lowering the levels of high values of the enzymes AST, ALT and ALP.…”
Section: Effect Of Se-nps and Se-nps + D3 In Immunosuppressed Rats Gi...supporting
confidence: 91%
“…The stimulatory effects of CMVIG, CMV lysate, and CMVIG-opsonized CMV lysate were observed at low concentrations of cyclosporine A (Figure 7 ) and tacrolimus (Figure S4, SDC, http://links.lww.com/TXD/A374 ) and were comparably inhibited by higher concentrations of calcineurin inhibitors (Figures 7 and Figure S4, SDC, http://links.lww.com/TXD/A374 ). Of note, the target blood level of cyclosporine A in transplant recipients usually ranges from 100 to 800 ng/mL, 58 - 61 which corresponds to molar concentrations ranging from 0.083 to 0.664 μM. This precisely corresponds to the range of cyclosporine A concentrations showing weak to strong inhibition of PBMC response in our ELISpot assay (Figure 7 ).…”
Section: Resultsmentioning
confidence: 74%
“…com/TXD/A374) and were comparably inhibited by higher concentrations of calcineurin inhibitors (Figures 7 and Figure S4, SDC, http://links.lww.com/TXD/A374). Of note, the target blood level of cyclosporine A in transplant recipients usually ranges from 100 to 800 ng/mL, [58][59][60][61] concentrations showing weak to strong inhibition of PBMC response in our ELISpot assay (Figure 7).…”
Section: Sensitivity Of Cmvig-treated Pbmcs To Immunosuppressionmentioning
confidence: 99%
“…Fluconazole was also prescribed recently for patients with diabetes mellitus [10]. Interestingly, fluconazole possesses unique and distinguished pharmacokinetic characteristics [3,4,11] in comparison to many other widely used drugs such as azithromycin [12], betahistine [13], doxazocin [14], cefixime [15], cyclosporine [16], amlodipine, valsartan, and hydrochlorothiazide [17]. There is a close similarity in the fluconazole's pharmacokinetics after intravenous, oral tablets, and oral suspension.…”
Section: Introductionmentioning
confidence: 99%
“…On the other extreme, If the given dose of the antimicrobial agent yields plasma levels above the maximum therapeutic levels, consequently drug therapy will be associated with adverse effect(s) which lead to stopping the drug usage, and replacement by other antimicrobial, or using a combination of antimicrobial agents which have many negative sides in term of the health and cost to the patient [12,15,[18][19][20]. Therefore, many pharmacokinetics, bioavailability, and bioequivalence researches were conducted in different countries and for almost all drugs to know the pharmacokinetic behaviors of the drug in each nation [12][13][14][15][16][17][18][21][22][23][24][25][26][27][28][29]. Among the researches conducted for fluconazole in particular, were for Thai [21], Arabic [18,22,23], Brazilian [24], Spanish [25], Serbian [26], Mexican [27], Bangladeshi [28], and Chinese individuals [29].…”
Section: Introductionmentioning
confidence: 99%